Association between dietary patterns reflecting one-carbon metabolism nutrients intake before pregnancy and placental DNA methylation. Issue 7 (3rd July 2022) - Lecorguillé, Marion; Charles, Marie-Aline; Lepeule, Johanna; Lioret, Sandrine; de Lauzon-Guillain, Blandine; Forhan, Anne; Tost, Jörg; Suderman, Matthew; Heude, Barbara
ABSTRACT: The preconception period represents an important window for foetal and epigenetic programming. Some micronutrients (B vitamins, choline, betaine, methionine) implicated in one-carbon metabolism (OCM) are essential for major epigenetic processes that take place in early pregnancy. However, few studies have evaluated the implication of the micronutrients in placental DNA methylation. We investigated whether intake of OCM nutrients in the year before pregnancy was associated with placental DNA methylation in the EDEN mother–child cohort. Maternal dietary intake was assessed with a food-frequency questionnaire. Three dietary patterns, 'varied and balanced diet, ' 'vegetarian tendency, ' and 'bread and starchy food, ' were used to characterize maternal OCM dietary intake. The Illumina Infinium HumanMethylation450 BeadChip was used to measure placental DNA methylation of 573 women included in the analyses. We evaluated the association of dietary patterns with global DNA methylation. Then, we conducted an agnostic epigenome-wide association study (EWAS) and investigated differentially methylated regions (DMRs) associated with each dietary pattern. We found no significant association between the three dietary patterns and global DNA methylation or individual CpG sites. DMR analyses highlighted associations between the 'varied and balanced' or 'vegetarian tendency' pattern and DMRs located at genes previously implicated in functions essential for embryonic development, such as neurodevelopment. The 'bread and starchy food' pattern was associated with regions related to genes whose functions involve various metabolic and cell synthesis-related processes. In mainly well-nourished French women without major deficiencies, OCM intake before pregnancy was not associated with major variation in DNA methylation.